LncMPEG1/miR-2c regulates exoskeleton biocalcification via engrailed in bivalve - Minxin Liang; Caixia Cai; Ziqi Ren; Zhiqing Li; Ronglian Huang; Qingheng Wang; Yongshan Liao; Chuangye Yang; Zhe Zheng (Aquaculture Reports)
LncRNAs and miRNAs has been reported to play important regulation roles in skeleton growth. This research elucidates the molecular interplay between long noncoding RNA LncMPEG1 and miRNA miR-2c in the biocalcification process of shell formation. The study establishes LncMPEG1 as a molecular sponge for miR-2c, modulating the expression of key biomineralization genes, including homeobox protein engrailed and matrix metalloproteases (MMPs). Utilizing miRanda prediction, interaction sites between miR-2c and LncMPEG1 were identified and validated through RNA immunoprecipitation and luciferase assays. In vivo overexpression of miR-2c suppressed engrailed and MMP expression, while miR-2c inhibition induced the opposite effect. Luciferase assays confirmed miR-2c's inhibitory effect on the 3′UTR of target genes (p < 0.001). Western blot analysis corroborated these findings, showing miR-2c's regulatory impact on protein expression levels. LncMPEG1 interference significantly reduced target gene transcription (p < 0.01), and its overexpression enhanced the reporter vector's activity by binding miR-2c (p < 0.05). Collectively, these results underscore LncMPEG1's role in shell formation through competitive binding with miR-2c, thereby regulating the expression of biomineralization-related genes.